2021
DOI: 10.1002/brb3.2402
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide‐related neurological disorders: Clinical, laboratory, neuroimaging, and electrophysiological findings

Abstract: Background: Recreational N 2 O abuse is an important etiology of neurological impairment in young patients, which may easily be ignored clinically. Few current studies have investigated the characteristics or the effects experienced by its users. We aimed to explore any correlation between the clinical severity and biomarkers and spinal magnetic resonance imaging (MRI) abnormalities, identify independent factors associated with spinal MRI abnormalities, and ascertain factors affecting depression/anxiety in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…It's difficult to differentiate N 2 O abuse and AMAN according to those electrophysiological findings ( 10 ). Meanwhile, the injury severity of lower limbs is usually heavier than the upper limbs in N 2 O abuser while it is similar in patient with GBS ( 11 ). The difference in the distal and proximal compound muscle action potential amplitudes of the upper limbs can be a parameter for differential diagnosis between the N 2 O abuser and AMAN patients, as the axonal injury was more severe in AMAN patients than N 2 O abuser, especially upper limbs ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…It's difficult to differentiate N 2 O abuse and AMAN according to those electrophysiological findings ( 10 ). Meanwhile, the injury severity of lower limbs is usually heavier than the upper limbs in N 2 O abuser while it is similar in patient with GBS ( 11 ). The difference in the distal and proximal compound muscle action potential amplitudes of the upper limbs can be a parameter for differential diagnosis between the N 2 O abuser and AMAN patients, as the axonal injury was more severe in AMAN patients than N 2 O abuser, especially upper limbs ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…The FDRS score was to quantify the severity of clinical manifestations and the effect on physical activity in SCDs, including N 2 O-related neuropathies (11,13,14). There may be objective factors related to the FDRS sum score, such as demographic characteristics, N 2 O consumption, hospitalization characteristics, imaging, and laboratory results.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the clinical evaluations, the functional disability rating score (FDRS) was calculated by two experienced neurologists. The score has been used widely in the clinical severity evaluation of SCDs, including N 2 Orelated neuropathies (11,13,14). The five-part scoring system is described as follows: (1) gait (0 = normal, 1 = positive Romberg's sign, 2 = impaired but able to walk unsupported, 3 = substantial support required for ambulation, 4 = wheelchair-bound or bedridden); (2) sensory disturbances including hypesthesia, dysesthesia, vibration/joint-position impairment (0 = normal, 1 = impairment only in toes and fingers, 2 = impairment in the ankles and wrists, 3 = impairment in the upper arms and legs); (3) mental impairment (0 = normal, 1 = intellectual or behavioral impairment requiring no social support, 2 = partial dependence for all activities of daily living, 3 = complete dependence for all activities of daily living); ( 4) neuropathy (0 = normal reflex, 1 = loss or reduction of deep tendon reflexes of the ankle, 2 = loss or reduction of deep tendon reflexes of the patella, 3 = loss or reduction of deep tendon reflexes of the biceps); and (5) pyramidal tract signs (0 = normal, 1 = positive Babinski sign, 2 = spastic paraparesis, 3 = spastic tetraparesis).…”
Section: Demographic and Clinical Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous recent reports of nitrous-oxide abusers with normal serum vitamin B12 levels who developed symptoms associated with vitamin B12 deficiency, such as neurological symptoms, subacute combined degeneration (SCD), and megaloblastic anemia [ 8 , 9 ]. The main reason for normal serum vitamin B12 levels in such patients is that the current clinical-test results reflect the total serum vitamin B12 level, in which only a small proportion of biotin B12 is active and shows a dynamic change; when active vitamin B12 deficiency occurs, the total serum vitamin B12 level can still be within the normal range [ 10 ]. Capdevila et al [ 11 ] reported that there was no linear correlation between the degree of neurological damage and serum vitamin B12 levels.…”
Section: Discussionmentioning
confidence: 99%